A method for preparing high-strength, high-toughness, corrosion-resistant Al-Cu-Li alloy

By adopting three-stage homogenization treatment, two-stage solid solution quenching and artificial aging treatment, combined with reasonable element composition, the problems of insufficient strength, toughness and corrosion resistance of Al-Cu-Li aluminum-lithium alloy in aerospace manufacturing are solved, and high-strength, high-strength, high-strength, corrosion-resistant alloy preparation is achieved.

CN116445782BActive Publication Date: 2025-05-02CHANGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310432015.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-21
Publication Date
2025-05-02
Estimated Expiration
2043-04-21

AI Technical Summary

Technical Problem

The existing Al-Cu-Li aluminum-li alloys have problems with insufficient strength, toughness and corrosion resistance in aerospace manufacturing, and it is difficult to achieve dimensional targets and performance uniformity during the manufacturing process.

Method used

Three-stage homogenization treatment and two-stage solid solution quenching process were adopted, and reasonable element composition (Cu 3.0-4.5%, Li 0.7-1.8%, Zr 0.08-0.16%, Mg 0.2-0.5%, Zn 0.4-0.7%, In 0.05-0.18%) were combined, and artificial aging was carried out to improve the strength, toughness and corrosion resistance of the alloy.

Benefits of technology

The strength, toughness and corrosion resistance of Al-Cu-Li alloys are significantly improved, ensuring the uniformity of performance and dimensional goals of the alloys are achieved, and are suitable for the field of aerospace manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004190607090000061
    Figure BDA0004190607090000061
  • Figure BDA0004190607090000071
    Figure BDA0004190607090000071
  • Figure BDA0004190607090000072
    Figure BDA0004190607090000072
Patent Text Reader

Abstract

The present invention relates to a novel alloy for aerospace, specifically a method for preparing a high-strength, high-toughness, and corrosion-resistant Al‑Cu‑Li alloy. The composition of the high-strength, high-toughness, and corrosion-resistant Al‑Cu‑Li alloy is as follows by mass percentage: Cu 3.0-4.5%, Li 0.7-1.8%, Zr 0.08-0.16%, Mg 0.2-0.5%, Zn 0.4-0.7%, In 0.05-0.18%, the total amount of impurity elements is ≤0.15%, and the balance is Al. The ingot is subjected to a three-stage homogenization treatment and then hot-rolled and cold-rolled to obtain a plate, which is subjected to a two-stage solid solution and quenching treatment and finally artificially aged. The present invention can effectively improve the tensile strength, elongation, and corrosion resistance of the Al‑Cu‑Li alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a new material, in particular to an alloy for aerospace, and specifically to the preparation of a high-strength, high-toughness, and corrosion-resistant Al-Cu-Li alloy. Background Art

[0002] According to statistics, the rapid development of aerospace technology is inseparable from the improvement of metal material performance. Aerospace vehicles can obtain more than 10 times the economic benefits for every 1kg weight reduction. Aluminum is the most abundant metal on earth, while lithium is the lightest metal on earth. After adding lithium to aluminum alloy, excellent properties such as high specific strength and specific stiffness can be obtained. However, the poor plasticity, low fracture toughness and short transverse strength of aluminum-lithium alloys, as well as high anisotropy of mechanical properties, hinder the promotion and application of aluminum-lithium alloys in the aerospace industry. In order to solve these problems, microalloying is one of the widely used and effective methods. A large number of studies have shown that adding certain trace or even trace elements (mole fraction is generally around 0.1%) to aluminum-lithium alloys has a very significant effect on improving the organization and properties of the alloy. At present, the development of aluminum-lithium alloys has formed the third generation of aluminum-lithium alloys with Al-Cu-Li as the main alloy system, which has the remarkable characteristics of low density, high modulus and high strength, and also has good corrosion resistance and high / low temperature performance. In the context of long-term structural weight reduction needs in the field of aerospace manufacturing, the application of Al-Cu-Li alloys can bring considerable benefits.

[0003] For Al-Cu-Li series aluminum alloys that can be strengthened by heat treatment, aging treatment can slowly precipitate various solute atoms in the supersaturated solid solution obtained after solution quenching, thereby forming precipitation phases (such as θ′(Al2Cu) phase, T1(Al2CuLi) phase, etc.), so that the strength and toughness of the alloy are improved. The composition, distribution and morphology of this multiphase structure are easily disturbed by the material processing and preparation process, thus forming a microstructure that weakens the performance during the manufacturing process, such as surface coarse grain layer, grain boundary segregation precipitation, etc. This also makes it difficult to achieve the size target and performance uniformity in the industrial production of Al-Cu-Li series aluminum-lithium alloy sheets. The In element also plays an extremely important role in aluminum-lithium alloys. In can refine the δ' and S phases, and will form In-Li-vacancy atomic groups in aluminum-lithium alloys, which capture a large number of Li atoms, resulting in slower nucleation of the δ' phase. During early aging, the T1 phase will nucleate at fine In particles. In addition, the addition of In may also promote the precipitation of cubic phase and θ' phase because In captures a large number of vacancies, inhibits the precipitation of T1 phase, and increases the precipitation advantage of other phases. At present, the amount of In used in aluminum alloy is large, the cost is high, and the effect is difficult to achieve as expected. Summary of the invention

[0004] In view of the problems in the background technology, the purpose of the present invention is to provide a method for preparing a high-strength, high-toughness, and corrosion-resistant Al-Cu-Li alloy plate.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] The invention discloses a method for preparing a high-strength, high-toughness, and corrosion-resistant Al-Cu-Li alloy plate. The high-strength, high-toughness, and corrosion-resistant Al-Cu-Li alloy comprises the following components by mass percentage: 3.0-4.5% Cu, 0.7-1.8% Li, 0.08-0.16% Zr, 0.2-0.5% Mg, 0.4-0.7% Zn, 0.05-0.18% In, the total amount of impurity elements is ≤0.15%, and the balance is Al.

[0007] The method comprises the following steps: after the ingredients are calculated, a high-purity aluminum ingot with an aluminum content greater than 99.9% is added into a high-purity graphite crucible, and the ingot is placed in a resistance furnace for heating at a temperature of 750°C to 810°C. After the high-purity aluminum is completely melted, 99.99% pure Cu, 99.99% pure Li, 99.99% pure Zn, 99.99% pure Mg, 99.99% pure In and Al-13wt.% Zr master alloy are added in sequence. A 25wt% LiF+75wt% LiCl covering agent is added to prevent burning. After the master alloy is completely melted, a high-purity graphite rod is used for full stirring, and the slag is removed after hexachloroethane degassing. The temperature is adjusted to 720°C to 740°C and then allowed to stand for 5 to 15 minutes. The molten melt after standing is poured into an iron mold, the ingot is subjected to a three-stage homogenization treatment, and then hot-rolled and cold-rolled to obtain a plate. The plate is subjected to a two-stage solid solution and quenching treatment, and finally subjected to an artificial aging treatment.

[0008] The present invention adopts a three-stage homogenization treatment ingot for high-strength, high-toughness and corrosion-resistant Al-Cu-Li alloy. The three-stage homogenization treatment is that the ingot is placed in a box-type resistance furnace for homogenization treatment at 450-470℃ / 5-8h+505-520℃ / 5-8h+520-540℃ / 20-28h. After the ingot is homogenized, the ingot is cut with a sawing machine and the surface is milled with a milling machine to remove shrinkage cavities in the casting process and surface oxides generated in the homogenization process.

[0009] The three-stage homogenization can not only effectively eliminate the internal stress of the ingot, effectively reduce the segregation of elements such as Cu and Mg in the ingot, and reduce the content of undissolved coarse residual phases at the grain boundaries. Long-term temperature gradient homogenization treatment cannot completely eliminate the insoluble aluminum-copper-iron-manganese impurity phase (Al7Cu2(Fe, Mn)x). It can only be broken and evenly distributed through subsequent rolling deformation, and the residual crystalline phase in the aluminum-lithium alloy ingot can be fully dissolved, and the dispersed phase can be evenly distributed, thereby providing a good billet structure for the subsequent blanking processing and rolling forming process of the ingot, and no annealing homogenization annealing is required during the rolling forming process. In actual operation, after the Al-Cu-Li alloy ingot undergoes three-stage homogenization heat treatment, the head and tail are sawed and the surface is milled to form an ingot.

[0010] Hot rolling, cold rolling to obtain plates: the ingot is first heated and kept warm to 430-480℃ / 1-4h. Before hot rolling, the rollers of the rolling mill are preheated for half an hour using a liquefied gas spray gun. After the rollers are preheated, rolling oil is brushed on their surfaces to lubricate the rollers; hot rolling is performed to obtain plates with a thickness of 5-10mm; and then cold rolling is performed to obtain plates with a thickness of 1-2.5mm.

[0011] In the further hot rolling process, the surface temperature of the plate is not lower than 330° C., the pass reduction rate in the hot rolling process is 10-30%, and the pass reduction rate in the cold rolling process is 5-15%.

[0012] The double-stage solid solution is 490-510℃ / 0.5-1h+510-530℃ / 0.5-1h. If the temperature is too low, the solid solution is not thorough, and if the temperature is too high, it is easy to cause overburning. The double-stage solid solution condition is given priority, which can achieve thorough solid solution without overburning.

[0013] In the present invention, the three-stage homogenization treatment and two-stage solid solution of the alloy are the key to the present invention. If the three-stage homogenization treatment, two-stage solid solution and reasonable component setting of the present invention are not followed, the effect of the present invention cannot be achieved. If single-stage and two-stage homogenization are used, it is easy to make the coarse phase in the alloy too much, which will affect other properties of the alloy. Three-stage homogenization + two-stage solid solution makes the alloy dissolve more fully.

[0014] Among them, quenching is water quenching to room temperature, and the quenching transfer time is less than 5s.

[0015] The temperature of artificial aging is 150-180°C, and the time is 0-300h.

[0016] The beneficial effects of the present invention are:

[0017] (1) The present invention adopts the above-mentioned process to perform three-stage homogenization treatment on the ingot before rolling the Al-Cu-Li alloy, which can not only effectively eliminate the internal stress of the ingot, prevent the ingot from cracking, reduce the homogenization time, and save energy, but also fully dissolve the residual crystalline phase in the aluminum-lithium alloy ingot and achieve the effect of uniform distribution of the dispersed phase, thereby providing a good ingot for the subsequent blanking processing and rolling forming process of the ingot.

[0018] (2) The present invention adds a reasonable component of 0.05-0.18% In to the Al-Cu-Li alloy and adopts the aging process of the Al-Cu-Li alloy, resulting in a method for preparing a high-strength, high-toughness, and corrosion-resistant Al-Cu-Li alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The stress-strain curves of Examples 1 to 3 of the present invention and Comparative Examples 1 to 3 are shown.

[0020] Figure 2 It is a diagram of the maximum corrosion depth of the intergranular corrosion experiments of Examples 1 to 3 of the present invention and Comparative Examples 1 to 3. DETAILED DESCRIPTION

[0021] The present invention is further described below in conjunction with the embodiments and comparative examples, but is not limited thereto. The alloy components are recorded by mass percentage as follows: Cu 3.0-4.5%, Li 0.7-1.8%, Zr 0.08-0.16%, Mg 0.2-0.5%, Zn 0.4-0.7%, In 0.05-0.18%, the total amount of impurity elements is ≤0.15%, and the balance is Al.

[0022] The alloy components used in the following examples are recorded by mass percentage as follows: Cu 4.09%, Li 1.66%, Zr 0.12%, Mg 0.28%, Zn 0.54%, In 0.17%, the total amount of impurity elements is ≤0.15%, and the balance is Al. The alloy components used in the comparative example are recorded by mass percentage as follows: Cu 4.11%, Li 1.63%, Zr 0.13%, Mg 0.30%, Zn 0.54%, the total amount of impurity elements is ≤0.15%, and the balance is Al.

[0023] Example 1

[0024] The Al-Cu-Li alloy ingot is first heated to 460℃ / 6h+515℃ / 6h+530℃ / 24h, then the head and tail are sawed and the surface is milled to form a hot-rolled ingot, and the ingot is heated to 460℃ with the furnace and kept warm for 2h. At the same time, the rollers are preheated and lubricated. The ingot is rolled into a plate with a thickness of 6mm. The surface temperature of the plate is not lower than 330℃ during the rolling process, and the pass reduction rate is 20% during the rolling process; the hot-rolled plate is cold-rolled to a 2mm plate by a cold rolling mill, and finally the cold-rolled plate is subjected to a two-stage solid solution and quenching treatment of 505℃ / 0.75h+520℃ / 0.75h, and then an artificial aging treatment of 150℃ / 124h is performed to obtain the final aluminum-lithium alloy plate.

[0025] Example 2

[0026] The Al-Cu-Li alloy ingot is first heated to 460℃ / 6h+515℃ / 6h+530℃ / 24h, then the head and tail are sawed and the surface is milled to form a hot-rolled ingot, and the ingot is heated to 460℃ with the furnace and kept warm for 2h. At the same time, the rollers are preheated and lubricated. The ingot is rolled into a plate with a thickness of 6mm. The surface temperature of the plate is not lower than 330℃ during the rolling process, and the pass reduction rate is 20% during the rolling process; the hot-rolled plate is cold-rolled to a 2mm plate by a cold rolling mill, and finally the cold-rolled plate is subjected to a two-stage solid solution and quenching treatment of 505℃ / 0.75h+520℃ / 0.75h, and then an artificial aging treatment of 165℃ / 115h is performed to obtain the final aluminum-lithium alloy plate.

[0027] Example 3

[0028] The Al-Cu-Li alloy ingot is first heated to 460℃ / 6h+515℃ / 6h+530℃ / 24h, then the head and tail are sawed and the surface is milled to form a hot-rolled ingot, and the ingot is heated to 460℃ with the furnace and kept warm for 2h. At the same time, the rollers are preheated and lubricated. The ingot is rolled into a plate with a thickness of 6mm. The surface temperature of the plate is not lower than 330℃ during the rolling process, and the pass reduction rate is 20% during the rolling process; the hot-rolled plate is cold-rolled to a 2mm plate by a cold rolling mill, and finally the cold-rolled plate is subjected to a two-stage solid solution and quenching treatment at 505℃ / 0.75h+520℃ / 0.75h, and then an artificial aging treatment at 180℃ / 26h is performed to obtain the final aluminum-lithium alloy plate.

[0029] Comparative Example 1

[0030] The Al-Cu-Li alloy ingot is first heated to 460℃ / 6h+515℃ / 6h+530℃ / 24h, then the head and tail are sawed and the surface is milled to form a hot-rolled ingot, and the ingot is heated to 460℃ with the furnace and kept warm for 2h. At the same time, the rollers are preheated and lubricated. The ingot is rolled into a plate with a thickness of 6mm. The surface temperature of the plate is not lower than 330℃ during the rolling process, and the pass reduction rate is 20% during the rolling process; the hot-rolled plate is cold-rolled to a 2mm plate by a cold rolling mill, and finally the cold-rolled plate is subjected to a two-stage solid solution and quenching treatment of 505℃ / 0.75h+520℃ / 0.75h, and then an artificial aging treatment of 150℃ / 92h is performed to obtain the final aluminum-lithium alloy plate.

[0031] Comparative Example 2

[0032] The Al-Cu-Li alloy ingot is first heated to 460℃ / 6h+515℃ / 6h+530℃ / 24h, then the head and tail are sawed and the surface is milled to form a hot-rolled ingot, and the ingot is heated to 460℃ with the furnace and kept warm for 2h. At the same time, the rollers are preheated and lubricated. The ingot is rolled into a plate with a thickness of 6mm. The surface temperature of the plate is not lower than 330℃ during the rolling process, and the pass reduction rate is 20% during the rolling process; the hot-rolled plate is cold-rolled to a 2mm plate by a cold rolling mill, and finally the cold-rolled plate is subjected to a two-stage solid solution treatment and quenching treatment at 505℃ / 0.75h+520℃ / 0.75h, and then an artificial aging treatment at 165℃ / 74h is performed to obtain the final aluminum-lithium alloy plate.

[0033] Comparative Example 3

[0034] The Al-Cu-Li alloy ingot is first heated to 460℃ / 6h+515℃ / 6h+530℃ / 24h, then the head and tail are sawed and the surface is milled to form a hot-rolled ingot, and the ingot is heated to 460℃ with the furnace and kept warm for 2h. At the same time, the rollers are preheated and lubricated. The ingot is rolled into a plate with a thickness of 6mm. The surface temperature of the plate is not lower than 330℃ during the rolling process, and the pass reduction rate is 20% during the rolling process; the hot-rolled plate is cold-rolled to a 2mm plate by a cold rolling mill, and finally the cold-rolled plate is subjected to a two-stage solid solution and quenching treatment at 505℃ / 0.75h+520℃ / 0.75h, and then an artificial aging treatment at 180℃ / 26h is performed to obtain the final aluminum-lithium alloy plate.

[0035] According to the determination method of the metal material tensile test in the national standard "GB / T 228.1-2010" and the intergranular corrosion test of aluminum alloy in the national standard "GB / T 7998-2005", the prepared example alloy and comparative alloy materials were tested, and each sample was tested three times to ensure the accuracy of the experimental data. The tensile strength and elongation at break of the above-mentioned example alloy and comparative alloy are shown in Table 1, and the intergranular corrosion test results are shown in Table 2.

[0036] Table 1 Room temperature mechanical properties test results of the embodiments of the present invention and the comparative examples

[0037]

[0038]

[0039] Table 2 Test results of intergranular corrosion of the embodiments of the present invention and the comparative examples

[0040]

[0041] By comparing the mechanical properties and corrosion performance test results of Examples 1 to 3 and Comparative Examples 1 to 3 and the attached Figures 1-2 It can be seen from the comparison that the embodiments of the present invention with the same aging strengthening state can significantly improve the mechanical properties and corrosion resistance of the embodiment alloy compared with the comparative example.

[0042] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the scope of implementation of the present invention. Those skilled in the art can make several improvements and substitutions based on the technical solution of the present invention without making any creative efforts. These improvements and substitutions all fall within the protection scope of the present invention.

Claims

1. A method for preparing a high-strength, high-toughness, corrosion-resistant Al-Cu-Li alloy, characterized in that: The following steps are involved: After the Al-Cu-Li alloy ingot is cast, it is first subjected to a three-stage homogenization treatment and then hot-rolled and cold-rolled to obtain a plate. The plate is subjected to a two-stage solid solution and quenching treatment and finally artificial aging treatment to obtain a high-strength, high-toughness, and corrosion-resistant Al-Cu-Li alloy. The three-stage homogenization treatment is that the ingot is placed in a box-type resistance furnace for homogenization treatment at 450-470℃ / 5-8h+505-520℃ / 5-8h+520-540℃ / 20-28h; the two-stage solid solution condition is 490~510℃ / 0.5-1h+510-530℃ / 0.5-1h; The composition of the high-strength, high-toughness and corrosion-resistant Al-Cu-Li alloy is as follows by mass percentage: Cu 3.0~4.5%, Li 0.7~1.8%, Zr 0.08~0.16%, Mg 0.2~0.5%, Zn 0.4~0.7%, In 0.05~0.18%, the total amount of impurity elements is ≤0.15%, and the balance is Al.

2. The method for preparing the high-strength, high-toughness, corrosion-resistant Al-Cu-Li alloy according to claim 1, characterized in that: After the three-stage homogenization treatment, the ingot is cut by sawing machine and milled by milling machine to remove shrinkage cavities in the casting process and surface oxides generated in the homogenization process.

3. The method for preparing the high-strength, high-toughness, corrosion-resistant Al-Cu-Li alloy according to claim 1, characterized in that: The hot rolling conditions are as follows: the ingot is first heated to 430~480℃ and kept warm for 1-4h. Before hot rolling, the rollers of the rolling mill are preheated for half an hour using a liquefied gas spray gun. After the rollers are preheated, rolling oil is brushed on their surfaces to lubricate the rollers. The plate with a thickness of 5~10mm is obtained by hot rolling. Then, the plate with a thickness of 1~2.5mm is obtained by cold rolling.

4. The method for preparing the high-strength, high-toughness, corrosion-resistant Al-Cu-Li alloy according to claim 1, characterized in that: During the hot rolling process, the surface temperature of the plate is not lower than 330° C., the pass reduction rate during the hot rolling process is 10-30%, and the pass reduction rate during the cold rolling process is 5-15%.

5. The method for preparing the high-strength, high-toughness, corrosion-resistant Al-Cu-Li alloy according to claim 1, characterized in that: The quenching is water quenching to room temperature, and the quenching transfer time is less than 5s.

6. The method for preparing the high-strength, high-toughness, corrosion-resistant Al-Cu-Li alloy according to claim 1, characterized in that: The artificial aging temperature is 150-180° C., and the time is 0-300 hours.

Citation Information

Patent Citations

  • Preparation method for Al-Cu-Li series aluminum-lithium alloy plate

    CN110331351A

  • Multiple-heattreatment method of indium bearing 2090 alloy

    KR1020120045624A